Pesticide residue management in harvested capsules of small cardamom - Aparna Joseph (Department of agricultural entomology, College of agriculture, 2020)
ABSTRACT A study on “Pesticide residue management in harvested capsules of small cardamom, Elettaria cardamomum Maton.” was undertaken at .College of Agriculture, Vellayani and Cardamom Research Station, Pampadumpara during June 2019 to February 2020. The objectives were to document the pesticide use pattern in cardamom in .Idukki district and to evaluate the effect of different decontamination methods for the removal of pesticide residues from fresh and dry cardamom capsules. Field survey conducted among the farmers of .Idukki district revealed that quinalphos, dimethoate, chlorpyriphos, ethion, profenophos, monocrotophos, lambda cyhalothrin, cypermethrin, fenvalerate, thiodicarb, carbosulfan, imidacloprid thiamethoxam, bordeaux mixture, copper oxy chloride, carbendazim, mancozeb were the most commonly used pesticides. The pests recorded during the study include shoot/capsule borer Conogethes punctiferalis, cardamom thrips Sciothrips cardamomi, cardamom root grub, Basilepta fulvicorne, hairy caterpillar, Eupterote sp., lacewing bug, Stephanitis typicus, cardamom scale Aulacaspis sp. and cowpea pod bug, Riptortus pedestris. For the timely management of these pests farmers were using a prophylactic spraying of plant protection chemicals at 20 to 30 days interval. Most of the farmers depended on pesticide retailers as a source of technical information. The laboratory experiment was laid out in CRD to study the efficacy of different .decontamination techniques in removing pesticide residues from fresh and dry cardamom capsules. In fresh cardamom, washing with water for three times followed by shaking in 2 % sodium bicarbonate solution for ten minutes showed superiority over other treatments in the removal of pesticide residues (30.83 to 90.70 %) except carbendazim. The highest removal was observed in quinalphos (90.70 %) and the lowest removal was observed in imidacloprid (30.83%). Sodium bicarbonate solution removed residues of dimethoate, chlorpyriphos, profenophos, ethion, lambda cyhalothrin, cypermethrin, fenvalerate and carbendazim by 41.82, 58.04, 66.27, 66.42, 68.43, 60.10, 60.92 and 56.55 per cent respectively. The next best decontaminating agent was 2 % sodium carbonate, which removed 26.77-65.15 per cent pesticide residues from fresh cardamom. In dry cardamom capsules, the highest removal of residues was obtained by removing the outer covering of dry cardamom (Decortication) which removed 32.75 to 100 per cent residues. No residues of quinalphos, lambda cyhalothrin and cypermethrin were detected in seeds after decortication. Washing and cooking of dry capsules for ten minutes showed a significant reduction in residues of dimethoate (37.95 %) and carbendazim (79.77 %). The removal of residues ranged from 23.41 to 79.77 per cent. The third best treatment was washing in 2 % vinegar which removed 44.55 per cent residues of ethion. The study could be concluded that washing of fresh cardamom with water for three times followed by shaking in 2 % sodium bicarbonate solution for ten minutes showed the maximum removal of pesticide residues. Decortication was the effective treatment for removing pesticide residues from dry cardamom.